The State Agrarian Register as an Instrument of GIS-Driven Governance - YASHCHENKO, L. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
Problem setting. In the context of digital transformation of public administration, data increasingly becomes a core resource for policymaking and managerial decision-making. However, the lack of systematic integration of the spatial dimension significantly limits the effectiveness of evidence-based governance, particularly in spatially sensitive sectors such as agriculture. In Ukraine, geographic information systems are still mainly used as technical or cadastral tools, rather than as institutional components of governance architectures. Aim of the study is to provide a theoretical and applied justification of the State Agrarian Register as an institutional instrument of GIS-Driven Governance within the public management system of Ukraine’s agricultural sector. Results. The article conceptualizes GIS-Driven Governance as a new governance paradigm in which GIS acts as a core decision-making infrastructure rather than a supplementary technology. It is demonstrated that the State Agrarian Register functions as an economic geoinformation system integrating spatial, financial, production, and administrative data. The State Agrarian Register enables algorithmic decision-making, territorially differentiated state support, and post-control mechanisms based on spatial verification. The study also reveals the functional and institutional compatibility of the SAR with key elements of the EU Common Agricultural Policy. Conclusions. The State Agrarian Register is identified as one of the most advanced sectoral implementations of GIS-Driven Governance in Ukraine. It serves not only as a digital platform for agricultural support but also as an institutional gateway to the European spatially oriented agricultural governance model, providing a foundation for sustainable development, transparency, and efficient public resource allocation.